An Investigation of Secondary School Students’ Biodiversity Literacy Level - Hülya Aslan Efe; Rıfat Efe (UIN Sultan Aji Muhammad Idris Samarinda, 2022)
The quality of life sustained by human beings is largely possible thanks to the opportunities offered by the biodiversity resources in nature. It is widely accepted that the continuation of this lifestyle largely depends on the sustainable use of consumed and destroyed natural resources. Therefore, teaching biodiversity becomes an important element of science teaching. In this context, it is important to reveal the biodiversity literacy levels of the new generation. This study aims to investigate secondary school students’ biodiversity literacy levels. The descriptive survey method, one of the quantitative research methods, was used in the research. A total of 787 secondary school students studying at state schools during 2021-2022 academic year participated in the research. “Biodiversity Literacy Assessment Instrument” was used as a data collection tool in the study. Independent t-test was used to compare gender scores while one-way ANOVA was used to compare student scores based on their grades, students’ feelings about studying biodiversity, and understanding problems related to biodiversity. Tukey HSD test was used to determine the direction of significance in multiple comparisons. The findings revealed that while secondary school students’ scores for attitudes toward biodiversity were high, their biodiversity knowledge levels were low. Also, female students gained higher scores for “the conservation and importance of biodiversity”, “ethics and biodiversity” and “sustainability and biodiversity” sub-dimensions of biodiversity literacy scale in comparison to male students. Additionally, the study found that participant students’ biodiversity literacy scale scores differed based on students’ years of study. The study has implications for teaching biodiversity that include activities to help students take responsibility for the protection of biodiversity and the place of biodiversity in the national curriculum.